2020
DOI: 10.3390/cryst10090806
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Luminescence of Eu3+- and Gd3+-Doped Hydroxyapatite Ca10(PO4)6(OH)2

Abstract: Luminescence properties of europium-doped Ca10-xEux(PO4)6(OH)2 (xEu = 0, 0.01, 0.02, 0.10 and 0.20) and gadolinium-doped hydroxyapatite Ca9.80Gd0.20(PO4)6(OH)2 (HA), synthesized via solid-state reaction at T = 1300 °C, were investigated using scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR), and luminescence spectroscopy. Crystal structure characterization (from unit cell parameters determination to refined atomic positions) was achieved in the P63/m space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…TPCs are biomaterial particularly wanted for their biocompatibility in human biosystem [1], and for the possibility of different cation replacements at the sites typically occupied by Ca [11], giving rise to different products, employed as commercial cement and paste for bone replacement [13,14]. In this regard, they are preferred to the more common synthetic Ca 10 (PO 4 ) 6 (OH) 2 hydroxyapatite because of their brittle nature [15,16]. Recently, additional interest has been also devoted to a series of rare-earth-doped TCP that are largely investigated as possible optical materials for biosciences application [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…TPCs are biomaterial particularly wanted for their biocompatibility in human biosystem [1], and for the possibility of different cation replacements at the sites typically occupied by Ca [11], giving rise to different products, employed as commercial cement and paste for bone replacement [13,14]. In this regard, they are preferred to the more common synthetic Ca 10 (PO 4 ) 6 (OH) 2 hydroxyapatite because of their brittle nature [15,16]. Recently, additional interest has been also devoted to a series of rare-earth-doped TCP that are largely investigated as possible optical materials for biosciences application [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…The vibronic intensity seen in the RE ions such as Gd 3+ doped HAp is due to vibronically induced forced electric dipole transitions [34]. In the literature, Paterlini et al said that the type of vibronic sidebands seen in the Gd 3 + doped HAp was observed for the first time only in their own study [30]. The vibronic peaks seen in the emission spectrum of Gd 3+ doped HAp belong to Gd-O, PO 3À 4 and O-H ions.…”
Section: Photoluminescencementioning
confidence: 97%
“…The luminescence of Gd 3+ in host materials is not so diverse because Gd 3+ has a certain transition which is 6 P 7/2 -8 S 7/2 . It is well known that the Gd-doped HAp samples show strong UV luminescence and that the excitation and the emission spectra of the Gd-doped HAp displays narrow peaks as in 4 f-4 f transitions [30].…”
Section: Photoluminescencementioning
confidence: 99%
See 2 more Smart Citations